Philippine Fishing Journal. v.6. (Manila Philippine Management and Financial Controllers, Inc., 1968)
Devoted to the development of Scientific Fishing Industry
Keywords: Fisheries -- Aquaculture -- Philippines -- Serials; Agriculture -- Fishing -- Aquatic resources -- Philippines -- Serials